TINJAUAN MAQASID SYARIAH TERHADAP ISBAT NIKAH ANALISIS PENETAPAN HAKIM PENGADILAN AGAMA ARGA MAKMUR NOMOR 0110/PDT.P/2016/PA.AGM DAN NOMOR 0128/PDT.P/2016/PA.AGM - Armalina, Armalina (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
Maqasid  Syariah  is the  objective  of recommendation for Islamic law, while Isbat marriage  is the  endorsement  of marriages  that have been  held according  to Islamic Shari’a,  but not recorded by Religious Affairs Office (KUA) or the Marriage Registry Official (PPN) authorized. The compilation of Islamic Law which has the power  of Inpres limits the permissible  cases to be attributed. The formulation of this research  problem  is how the basis of judges’ consideration as well as how the analysis of maqasidsyariah to the determination of the case Number  0110  / Pdt.P  / 2016  / PA.AGM and  Number  0128  / Pdt.P  / 2016/ PA.AGM about  isbat marriage. The research  method was used  qualitative  descriptive  analysis  that was the data  processing obtained in the field study result which then combined with data  obtained from literature  study, in order  to obtainthe accurate data.  The approach was used  the juridical approach. The location  of the research  was conducted in Arga Makmur  Religious Court. Primary data  sources obtained through  interviews with Judges  involved in the establishment of isbat marriage. Second- ary data  sources  was included  the legislation and  court decisions,  coupled  with literature  relevant  to marriageisbat issues. The result of the research  was found  that judge consideration in the determination of case Number  0110  / Pdt.P  / 2016  / PA.AGM and Number  0128 / Pdt.P / 2016 / PA.AGM on marriage  isbat based  on juridical, philosophical and sociological considerations. The juridical isbat marriage  regulated in the Compilation of Islamic Law through  Presidential  Instruction  Number  1 of 1991. The determination of marriage  isbat was supported by the evidence  on the facts in the hearing.  Maqasid  sharia  in the case of marriage  isbat in Islamic law that is to realize and maintain mashlahat mankind on marital status and status of child in marriage.. The stipulation  of marriage  isbat provides  legal certainty to the legality of marriage  both religionally and legally